1995
DOI: 10.1007/bf01928896
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of 3-epi-22-deoxy-20-hydroxyecdysone and its phosphoric ester in diapause eggs of the silkworm,Bombyx mori

Abstract: Abstract. Ecdysteroids in diapause eggs of the silkworm, Bornbyx mori, were analyzed using high-performance liquid chromatography (HPLC) combined with radioimmunoassay (RIA). A relatively large amount of an unidentified free ecdysteroid and its phosphoric ester (conjugated form) were detected. These two compounds were isolated by a combination of column chromatography on silicic acid, thin-layer chromatography (TLC), and HPLC using a reverse-phase (RP) column. The purified compounds were identified as 3-epi-22… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…In the diapause eggs, the bulk of the ecdysteroids are conjugated forms (phosphoric esters), but in the non-diapause eggs free forms co-exist with the conjugated forms (Ohnishi et al, 1971(Ohnishi et al, 1977Mizuno et al, 1981;Mamiya et al, 1995;Sonobe et al, 1997). In the course of quantitative analysis of egg ecdysteroids in the silkworm, we found that the 20-hydroxyecdysone titer, which is thought to be a physiologically active molecule in the silkworm egg (Gharib et al, 1981a), in-creased sharply in the non-diapause eggs as embryonic development proceeded, but remained at a low level in the diapause eggs .…”
Section: Introductionmentioning
confidence: 99%
“…In the diapause eggs, the bulk of the ecdysteroids are conjugated forms (phosphoric esters), but in the non-diapause eggs free forms co-exist with the conjugated forms (Ohnishi et al, 1971(Ohnishi et al, 1977Mizuno et al, 1981;Mamiya et al, 1995;Sonobe et al, 1997). In the course of quantitative analysis of egg ecdysteroids in the silkworm, we found that the 20-hydroxyecdysone titer, which is thought to be a physiologically active molecule in the silkworm egg (Gharib et al, 1981a), in-creased sharply in the non-diapause eggs as embryonic development proceeded, but remained at a low level in the diapause eggs .…”
Section: Introductionmentioning
confidence: 99%
“…In the diapause eggs, the bulk of the ecdysteroids are conjugated forms (phosphoric esters), but in the non-diapause eggs free forms co-exist with the conjugated forms (Ohnishi et al, 1971(Ohnishi et al, 1977Mizuno et al, 1981;Mamiya et al, 1995;Sonobe et al, 1997). In the course of quantitative analysis of egg ecdysteroids in the silkworm, we found that the 20-hydroxyecdysone titer, which is thought to be a physiologically active molecule in the silkworm egg (Gharib et al, 1981a), in-creased sharply in the non-diapause eggs as embryonic development proceeded, but remained at a low level in the diapause eggs .…”
Section: Introductionmentioning
confidence: 99%
“…This compound was earlier isolated from diapause eggs of the silkworm Bombyx mori , but only partial 1 H NMR data supporting the proposed structure were reported [14]. The complete 1 H and 13 C NMR assignments are thus listed in Table 1.…”
Section: Resultsmentioning
confidence: 94%